The impact of technology use for care by informal female caregivers on their well-being: a scoping review - Andrés Aparicio; María Alejandra Inostroza-Correa; Paula Miranda; Carolina Salinas; Valeria Herskovic; Camila Chackiel; Catalina Alarcón (Systematic Reviews)
Abstract Introduction Informal caregiving roles are predominantly assumed by women, who often experience unique challenges related to physical, emotional, and social stress due to entrenched gender disparities. Within this context, the use of technologies to assist in caregiving tasks has become popular, and some evidence about their impact on caregiver well-being is available. However, significant research gaps persist. This scoping review was intended to assess the extent of literature examining the impact of technology use by informal female caregivers on their quality of life, to characterize existing research gaps, and to identify available evidence regarding gender-specific challenges. Methods We searched for studies in English, Spanish, and Portuguese published in peer-reviewed journals since 2018. We included studies exploring how informal female caregivers use technology and how such use impacts their well-being. The studies included in the review analyze the impact of technology use on the physical, emotional, or material well-being of informal female caregivers. Sources were screened in stages by two independent reviewers; data were extracted from selected full texts, and results were integrated into a narrative summary. Results A total of 14 studies were included in the review, highlighting a range of technologies such as health monitoring devices, communication platforms, and assistive aids. The review identified improvements in caregiver well-being related to reduced physical burden, enhanced emotional support, and increased social connectivity. However, significant research gaps were noted, particularly regarding the long-term effects of technology use, differences based on socio-economic contexts, and the limited inclusion of gender-specific analyses. Conclusions This review supports the notion that technology use can positively impact the well-being of informal female caregivers, especially in terms of emotional and social support. Nevertheless, the review also found that in certain situations, technology can fail to improve or even worsen the quality of life of caregivers. However, the limited availability of studies with standardized quantitative measures, gender-specific data, and comprehensive assessments of long-term effects highlights areas for future research. Further exploration into diverse sociocultural contexts and empirical model development will be essential to better understand the nuanced ways in which technology use influences caregiver quality of life. These findings underscore the potential for targeted technology solutions to support informal caregivers, with implications for healthcare professionals and policymakers designing caregiver support initiatives.